Ecos del pasado. Oralidad e historia antigua. Contribución de Juan Cascajero - David Espinosa Espinosa (Gerión, 2007)
The present work, framed in the affectionate tribute to the person and work of Juan Cascajero, tries to synthesize and to show a global vision of the historical development and the practice of the theoretical foundations of Oral History, in Spain, and its reflection in the historiographic task of Juan Cascajero, main defender of this tool of work, from the parcels of the knowledge of Old History, like means of approach to the conditions of spiritual existence, materials and, of the majorities, silenced, of the Antiquity.